Kinetic Characteristics of Nitriding of Zr–1% Nb Alloy - Trush, V. S.; Pohrelyuk, I. M.; Kravchyshyn, T. M.; Luk’yanenko, A. G.; Stoev, P. I.; Fedirko, V. M.; Kovalchuk, I. V. (Materials science (New York, N.Y.), 2022)
We study the kinetic characteristics of nitriding of thin-sheet (~ 1 mm) samples of Zr–1% Nb alloy treated in a nitrogen atmosphere ( ) in broad temperature ( T = 550; 650; 750; 850 and 950°С) and time ( τ = 1; 5 and 10 h) ranges. It is shown that the process of nitriding of the analyzed alloy obeys a law close to a parabolic dependence ( n ≈ 2). It is discovered that the activation energy of nitriding of the alloy within the temperature range 550–950°C is equal to 131.8 kJ/mole. The microstructure of the subsurface layer of the alloy after nitriding is analyzed. The distribution of the surface microhardness of Zr–1% Nb alloy is determined. The diagrams of intensity of the phase reflexes of α -Zr and ZrN on the surface of alloy after treatment in a nitrogen atmosphere are constructed.